HIV-infected men who have sex with men, before and after release from jail: the impact of age and race, results from a multi-site study. Issue 1 (2nd January 2016) - Vagenas, Panagiotis; Zelenev, Alexei; Altice, Frederick L.; Di Paola, Angela; Jordan, Alison O.; Teixeira, Paul A.; Frew, Paula M.; Spaulding, Anne C.; Springer, Sandra A.
Abstract : The US HIV/AIDS epidemic is concentrated among men who have sex with men (MSM). Black men are disproportionately affected by incarceration and Black MSM experience higher infection rates and worse HIV-related health outcomes compared to non-Black MSM. We compared HIV treatment outcomes for Black MSM to other HIV-infected men from one of the largest cohorts of HIV-infected jail detainees ( N  = 1270) transitioning to the community. Of the 574 HIV-infected men released, 113 (19.7%) self-identified as being MSM. Compared to other male subgroups, young Black MSM (<30 years old, N  = 18) were significantly less likely: (1) before incarceration, to have insurance, access to an HIV healthcare provider, and use cocaine; (2) during incarceration, to receive a disease management intervention; and (3) in the 6 months post-release, to link to HIV care. Interventions that effectively link and retain young HIV-infected Black MSM in care in communities before incarceration and post-release from jail are urgently needed.